The practice of farming, processing and trading of tobacco by Sukasari people of Sumedang District, West Java, Indonesia - JOHAN ISKANDAR; BUDIAWATI S. ISKANDAR; AZRIL AZRIL; RUHYAT PARTASASMITA (Society for Indonesian Biodiversity, 2017)
Iskandar J, Iskandar BS, Azril, Partasasmita R. 2017. The practice of farming, processing and trading of tobacco by Sukasari people of Sumedang District, West Java, Indonesia. Biodiversitas 18: 1517-1527. Tobacco (Nicotiana tabacum L) is an original crop of Cuba, Latin America, discovered by Christoper Columbus in 1492 and introduced to Europe. Moreover, it was distributed to Asia countries, including Indonesia. Local people of Sukasari village, Sukasari sub-district, Sumedang district, West Java, has cultivated tobacco for a long time, since the Dutch colonial, based on local ecological knowledge transmitted by inter-generations. As a result, local people of Sukasari village have rich knowledge on the tobacco. Nowadays, however, since the agricultural lands as well as tobacco farmers have decreased, the local ecological knowledge of the Sukasari people have eroded. This paper elucidates the local ecological knowledge of Sukasari people, Sumedang District of West Java on landraces, cultivation, process, and local trading of tobacco. The method used in this study was qualitative with descriptive analysis applying the ethnoecological approach. The result of the study showed that the Sukasari people have predominantly cultivated four landraces of the tobacco. The cultivation of tobacco include the selecting of seeds, nursery, preparing land, planting, caring, harvesting and processing of tobacco products, requiring diligent efforts and high skill. Today, the cultivation of tobacco has many constrains, such as climate anomalies, decrease of agricultural lands, and the lack of finance; consequently, the tobacco farmers have less enthusiasm to cultivate the tobacco. As a result of decreaase of tobacco cultivation, the local ecological knowledge of the Sukasari people has eroded and may extinct in the near future.